Influence of fresh date palm co-products on the ripening of a paprika added dry-cured sausage model system - Ben-Abda, J. (2017)
Date palm co-products are a source of bioactive compounds that could be used as a new ingredient for the meat industry. An intermediate food product (IFP) from date palm co-products (5%) was incorporated into a paprika added dry-cured sausage (PADS) model system and was analysed for physicochemical parameters, lipid oxidation and sensory attributes during ripening. Addition of 5% IFP yielded a product with physicochemical properties similar to the traditional one. Instrumental colour differences were found, but were not detected visually by panellists, who also evaluated positively the sensory properties of the PADS with IFP. Therefore, the IFP from date palm co-products could be used as a natural ingredient in the formulation of PADS